2005
DOI: 10.1152/jn.01005.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Sound-Evoked Vestibulomasseteric Reflex in Healthy Humans

Abstract: Averaged responses to loud clicks were recorded in the unrectified and rectified masseter electromyogram (EMG) of 18 healthy subjects. Unilateral clicks (0.1 ms, 3 Hz, 70-100 dB NHL), delivered during a steady masseter contraction, evoked bilateral responses that appeared to consist of 2 components on the basis of threshold, latency, and their appearance in rectified EMG. The lowest threshold response appeared as a p16 wave (onset 11-13 ms) in the unrectified EMG and corresponded with a 10- to 12-ms period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 50 publications
5
82
0
1
Order By: Relevance
“…This observation provides an anatomical substrate to account for the finding that vestibular stimulation alters masseter muscle activity in animals (Tolu and Pugliatti 1993;Tolu et al 1994Tolu et al , 1996Deriu et al 1999) and humans (Hickenbottom et al 1985;Deriu et al 2000Deriu et al , 2003Deriu et al , 2005. All parts of the VN contained infected neurons following injections of PRV-BA into the masseter muscle, especially the caudal portion of the MVe and the SpVe; in addition, labeling was concentrated in the caudal PH.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…This observation provides an anatomical substrate to account for the finding that vestibular stimulation alters masseter muscle activity in animals (Tolu and Pugliatti 1993;Tolu et al 1994Tolu et al , 1996Deriu et al 1999) and humans (Hickenbottom et al 1985;Deriu et al 2000Deriu et al , 2003Deriu et al , 2005. All parts of the VN contained infected neurons following injections of PRV-BA into the masseter muscle, especially the caudal portion of the MVe and the SpVe; in addition, labeling was concentrated in the caudal PH.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, the muscle fibers associated with each masseter motor unit are limited to a relatively small region of the muscle, such that each masseter motoneuron provides innervation to a restricted territory (Weijs et al 1993). Our PRV-BA injections were made into the lower third of the superficial layer of the muscle, because this compartment receives the densest motor innervation (Godeaux and Desmedt 1975;Widmer and Lund 1989;Widmer et al 1997); in humans, the largest vestibular-induced EMG responses were detected when recording electrodes were positioned on this part of the muscle (Deriu et al 2003(Deriu et al , 2005. The compartments of the masseter muscle injected with PRV-BA in Fay and Norgren's study (Fay and Norgren 1997) were not discussed, such that the locations of their injections within the muscle could have differed from ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have shown that the activity of mandibular muscles is modulated by the vestibular system (Hickenbottom et al 1985;Tolu and Pugliatti 1993;Tolu et al 1994;Tolu et al 1996;Deriu et al 1999;Deriu et al 2003;Deriu et al 2005). In particular, experiments performed on guinea pigs demonstrated that stimulation of receptors in the semicircular canal ampullae elicits bilateral excitatory responses of masseter and digastric motoneurons and that macular inputs exert bilateral asymmetrical influences on jaw muscle activity.…”
Section: Introductionmentioning
confidence: 99%